1993
DOI: 10.1159/000187471
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Immunoadsorption on the Removal of Immunoglobulin G Autoantibodies in Crescentic Glomerulonephritis

Abstract: We report the treatment of 5 patients with crescentic glomerulonephritis by immunoadsorption using a protein A column. Two had systemic vasculitis, 2 antiglomerular basement membrane disease and 1 systemic lupus erythematosus (SLE). In the patients with systemic vasculitis and SLE, there was successful removal of autoantibodies and rapid control of disease; remission was maintained over a mean follow-up of 2 years. Clinical improvement was not seen in 2 patients with anti-glomerular basement membrane (GBM) dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Thus, considerably higher plasma volumes can be treated in 1 session without the side effects noted with plasma exchange. Consequently, elimination rates of pathologic antibodies are increased (12,13,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, considerably higher plasma volumes can be treated in 1 session without the side effects noted with plasma exchange. Consequently, elimination rates of pathologic antibodies are increased (12,13,15).…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of IA by both double‐column systems are convincing in theory, only a few clinical studies have been conducted (7,12,13). A recently published controlled and randomized Swedish study compared protein A IA with plasma exchange (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involving SLE patients are anecdotal (50–52), and protein A immunoadsorption was used mainly in conjunction with immunosuppressive therapy (42). In a recent study, the efficient removal of antibodies and CICs was shown to correlate with surface markers of lymphocytes and monocytes (52,53).…”
Section: Adsorption Apheresismentioning
confidence: 99%
“…There has been an improvement in the prognosis of PRS following the introduction of plasma exchange and immunosuppression; faster depletion of pathogenic autoantibodies using immunoadsorption with staphylococcal protein A or specific antibody removal against columns using recombinant antigens might have further advantages. 64,65 Of newer agents, intravenous immunoglobulin has led to recovery in refractory AASV, but there is no published experience in DPH. Prolonged antibiotic therapy with sulfamethoxazole/trimethoprim reduces relapse rates in WG, which is probably related to a reduction in the triggering effect of respiratory tract infection on vasculitis.…”
Section: Future Directionsmentioning
confidence: 99%